Pandemics and their impact on oil and metal prices - Tony Addison; Atanu Ghoshray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We examine the effect of pandemics on selected commodity prices-in particular, those of zinc, copper, lead, and oil. We set up a vector autoregressive model and analyse data since the mid-nineteenth century to determine how prices reacted to pandemics such as the 1918 Spanish Flu, 1957 Asian Flu, and 1968 Hong Kong Flu. We control for demand and supply fundamentals to generate forecasts from the point of outbreak, and we consider whether any pattern can be deduced in reactions to adverse global shocks. Results are varied, depending on choice of commodity and magnitude and type of response. No clear conclusions are possible from past pandemics, and we conclude that at the time of writing, forecasts are difficult to make in the ongoing current pandemic too. We conclude by estimating impulse response functions to assess likely impact and the subsequent response of commodity prices to the shock.
Keywords: C22; Q02; Q32; 330; pandemics; commodity prices; global shocks; vector autoregressive model (VAR)